2020
DOI: 10.21203/rs.3.rs-51984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-sensitive Long Noncoding RNA CASC15 Promotes Lung Tumorigenesis by Regulating the SOX4/β-catenin Axis

Abstract: Background: Accumulating evidence has demonstrated that long non-coding RNAs (lncRNAs) are involved in the hypoxia-related cancer process and play pivotal roles in enabling malignant cells to survive under hypoxic stress. However, the molecular crosstalk between lncRNAs and hypoxia signaling cascades in non-small cell lung cancer (NSCLC) remains largely elusive. Methods: Firstly, we identified differentially expressed lncRNA cancer susceptibility candidate 15 (CASC15) as associated with NSCLC based on bioinfor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Recently, a novel oncogenic lncRNA, CASC15, is identified in various cancers such as basal cell [13], hepatic [14,15] and tongue squamous cell carcinoma [16], as well as cervical [17], breast [18], melanoma [19][20][21], gastric [22,23], colon [24], lung [25] and ovarian [26] cancer. Nevertheless, previously published studies on the effect of lncRNA CASC15 in ovarian cancer [26,27] are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel oncogenic lncRNA, CASC15, is identified in various cancers such as basal cell [13], hepatic [14,15] and tongue squamous cell carcinoma [16], as well as cervical [17], breast [18], melanoma [19][20][21], gastric [22,23], colon [24], lung [25] and ovarian [26] cancer. Nevertheless, previously published studies on the effect of lncRNA CASC15 in ovarian cancer [26,27] are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Through binding with DNA, RNA, and proteins in the nucleus and cytoplasm, lncRNAs influence gene expression epigenetically, co-transcriptionally, and post-transcriptionally, acting as oncogenes [88][89][90][91][92][93][94] or tumor suppressors [95][96][97][98][99][100] in cancer, Figure 1, Table 1.…”
Section: Long Non-coding Rnamentioning
confidence: 99%
“…Through binding with DNA, RNA, and proteins in the nucleus and cytoplasm, lncRNAs influence gene expression epigenetically, co-transcriptionally, and post-transcriptionally, acting as oncogenes [88][89][90][91][92][93][94] or tumor suppressors [95][96][97][98][99][100] in cancer, Figure 1, Table 1. long intergenic non-coding RNAs (XIST, HOTTIP, ARIEL, LUNAR1 and others) interact with Polycomb complexes and other adapter proteins, form connections between transcriptional regulators and distal DNA sequences through DNA looping; lncRNAs transcribed from antisense to protein-coding genes DNA strands, e.g., AS-RBM15, PU.1-AS, regulate expression of these genes posttranscriptionally (d); both transcriptional and posttranscriptional mechanisms of action were described for some lncRNAs, e.g., HOTAIR, HOTAIRM1, UCA1, that regulate gene expression in their genomic locus (acting in cis), and distal genomic regions (acting in trans).…”
Section: Long Non-coding Rnamentioning
confidence: 99%
“…Under hypoxia conditions, AC020978 was proved to be induced in lung cancer cells and facilitate tumor proliferation and glycolytic metabolism through PKM2/HIF axis [16]. Sun et al reported that CASC15 might be sensitive to hypoxia and enhance cancer cell viability [17]. However, the features of prognostic markers of lung adenocarcinoma based on hypoxiaassociated lncRNAs have not been studied.…”
Section: Introductionmentioning
confidence: 99%